Geochemistry of Luala (LUL) peat core from Kitulo Plateau, Tanzania - Robert Marchant (PANGAEA, 2021)
Geochemistry data of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.